2021
DOI: 10.1186/s13041-020-00725-y
|View full text |Cite
|
Sign up to set email alerts
|

A CACNA1A variant associated with trigeminal neuralgia alters the gating of Cav2.1 channels

Abstract: A novel missense mutation in the CACNA1A gene that encodes the pore forming α1 subunit of the CaV2.1 voltage-gated calcium channel was identified in a patient with trigeminal neuralgia. This mutation leads to a substitution of proline 2455 by histidine (P2455H) in the distal C-terminus region of the channel. Due to the well characterized role of this channel in neurotransmitter release, our aim was to characterize the biophysical properties of the P2455H variant in heterologously expressed CaV2.1 channels. Who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Calcium channels are potential therapeutic targets for TN treatment, and calcium channel blockers such as gabapentin are used as alternatives to sodium channel blocker carbamazepine. 5 Gambeta et al 36 Molecular Pain channel, as well as strongly reduced calcium-dependent activation of the channel that is consistent with an overall gain of function. They suggested that the depolarizing shift in activation may be more important in neurons with lower firing rates, while the gain of function may have a more profound impact in neurons with high frequency firing.…”
Section: Human Studies On Genetics In Tnmentioning
confidence: 77%
See 2 more Smart Citations
“…Calcium channels are potential therapeutic targets for TN treatment, and calcium channel blockers such as gabapentin are used as alternatives to sodium channel blocker carbamazepine. 5 Gambeta et al 36 Molecular Pain channel, as well as strongly reduced calcium-dependent activation of the channel that is consistent with an overall gain of function. They suggested that the depolarizing shift in activation may be more important in neurons with lower firing rates, while the gain of function may have a more profound impact in neurons with high frequency firing.…”
Section: Human Studies On Genetics In Tnmentioning
confidence: 77%
“…Two studies propose that CACNA gene mutations (mutations in genes coding for calcium channels) are related to neuronal excitability, thus contributing to TN susceptibility or development. 35 , 36 CACNA1A gene mutation alters the gating properties of the channel, suggesting that associated changes in the Cav2.1-dependent synaptic communication in the trigeminal system may contribute to the development of TN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the existing literature, there is an increasing number of possible candidate genes in TN [5][6][7]. In particular, mutation in genes coding for voltage-gated ion channels (sodium, calcium, potassium and chloride) and TRP channels may alter neuronal excitability that increase susceptibility for developing TN [15,42,[45][46][47]. Siqueira et al [46] reported altered expression of voltage-gated sodium channels Na V 1.7, Na V 1.3, and Na V 1.8 in TN cases compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alterations of the expression of several ion channels including sodium, calcium, and potassium channels have been reported in TN patients [ 9 ] as well as in preclinical rodent models [ 10 17 ]. In addition, rare polymorphisms in ion channel genes were identified in TN patients [ 18 20 ] suggesting the existence of predisposing genetic factors and gain-of-function mutations (GoF) were reported for Na v 1.6 [ 18 ], Ca v 2.1 [ 21 ], TRPM7 [ 22 , 23 ], and TRPM8 channels [ 24 ].…”
Section: Introductionmentioning
confidence: 99%